New insight into the electrical properties and ion dynamics of screen printed NASICON thick films. Issue 23 (21st June 2015) - Mudenda, Steven; Kale, Girish M.
<x xml:space="preserve">Abstract</x> The AC conductivity of NASICON thick films at high temperatures and the relaxation mechanism are independent of film thickness. 7 μm is the minimum thickness that could be printed on alumina substrate and used in high temperature applications.